FREQUENCY OF LOW BONE MASS IN A COHORT OF MIXED PAKISTANI POPULATION: Frequency of Low Bone Mass - Akhlaque, Uzma; Ahmad, Khalil; Ahmad, Nadeem; Waheed, Akhtar; Akhtar, Noreen (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the frequency of low bone mass in a multiethnic group of Pakistani population at Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi. Study Design: Cross-sectional comparative study. Place and Duration of Study: Outpatient Department of Armed Forces Institute of Rehabilitation Medicine (AFIRM), Rawalpindi from October 2010 to March 2011. Subjects and Methods: A total of 400 patients, both male and female, were sampled according to inclusion criteria by non-probability purposive sampling. Bone density was measured by DXA scan model Hologic “Discovery A”, focused at neck of femur and spine. Results: Four hundred patients were included in the study. Average age of the patients was 59.24 years (SD = 10.38) with 258 (64.5%) females. Two hundred and thirty two (58%) were Punjabi, 77 (19.3%) were Pathan, 64 (16%) were Kashmiri, 20 (5%) were Sindhi and 7 (1.8%) were Balochi. Average BMI was 26.45 (SD = 5.31). Average T-score was -2.037 (SD = 1.40). Out of 400 patients, 134 (33.5%) patients had normal BMD, 140 (35%) had osteopenia and 126 (31.5%) patients had osteoporosis. Frequency of osteopenia was higher in males than females i.e. 40.8% vs. 31.8% whereas frequency of osteoporosis was higher in females than males i.e. 32.9% vs. 28.9% (p = 0.191). Similarly association between ethnicity and BMD was also observed to be insignificant (p = 0.714). Conclusions: The study showed high prevalence of low bone mass in Pakistani population in females as well as in males. The results in various ethnic groups are comparable, however, due to availability of smaller number of Sindhi and Balochi people, further multicentre studies at larger scale are recommended.